Fishing Business Performance Analysis: An Entrepreneurial Approach - Rusdiaman Rauf; Hengki Wijaya (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2022)
AbstractEntrepreneurship requires work motivation, entrepreneurial learning and entrepreneurship commitment to improving business performance in various types of businesses, especially in the business activities of fishing communities. This study used a purposeful sample of 70 respondents and focused on fishermen who use boats as fishing equipment in the sea. The results of the study indicate that work motivation and commitment to entrepreneurship directly and partially have a significant positive effect on business performance, while entrepreneurial learning has an insignificant effect, while simultaneously work motivation, entrepreneurial learning and commitment to entrepreneurship have a positive and significant effect on business performance. Keywords: Work motivation, entrepreneurial learning, entrepreneurial commitment, business performance Analisis Kinerja Usaha Penangkapan Ikan:Suatu Pendekatan Kewirausahaan AbstrakKewirausahaan membutuhkan motivasi kerja, pembelajaran kewirausahaan dan komitmen kewirausahaan untuk meningkatkan kinerja usaha di berbagai jenis usaha, terutama dalam kegiatan usaha masyarakat nelayan. Metode penelitian ini dilakukan secara purposive pada nelayan yang memiliki perahu sebagai alat tangkap ikan di laut dengan jumlah sampel 70 responden. Hasil penelitian menunjukkan bahwa motivasi kerja dan komitmen berwirausaha secara langsung dan parsial berpengaruh positif signifikan terhadap kinerja usaha, sedangkan pembelajaran kewirausahaan berpengaruh tidak signifikan, sedangkan secara simultan motivasi kerja, pembelajaran kewirausahaan dan komitmen berwirausaha berpengaruh positif dan signifikan. pada kinerja usaha. Kata kunci: Motivasi kerja, pembelajaran wirausaha, komitmen wirausaha, kinerja usaha